Perspectives on Environmental Humanities: Technology, Nature, and Human-Animal Relationships - Gašper Raušl; Finn Arne Jørgensen (Svetovi, 2025)
Finn Arne Jørgensen is a professor of environmental history at the University of Stavanger in Norway. He studies the evolution of human relationships with nature over time and place. His latest book, titled Sharing Spaces: Technology, Mediation, and Human-Animal Relationships (2024, University of Pittsburgh Press), explores how technology enables and mediates relationships between humans and nature.